Preparation of Pt dendrites on Poly(diallyldimethylammonium chloride)-functionalized reduced graphene oxide as an enhanced electrocatalyst for the hydrogen evolution reaction in alkaline media. (13th September 2019) - Kim, Seong-Hoon; Jaleel, Ahsan; Abbas, Syed Asad; Jung, Kwang-Deog
Abstract: Herein, we describe the synthesis of Pt dendrites with electrochemically active high-index planes on poly(diallyldimethylammonium chloride)-functionalized reduced graphene oxide (PFG) using a newly developed high-voltage electrochemical reduction (HVER) method. Subsequently, the catalytic activities of the prepared samples for the hydrogen evolution reaction (HER) in 1 M NaOH are characterized. The HVER method facilitates the preparation of nanoparticles in short reaction times. This method allows Pt particles to be formed by electron transfer from the cathode to a Pt precursor. Importantly, Pt particles deposited on PFG (Pt/PFG), prepared by the addition of PVP, are revealed to comprise both two- (2D) and three-dimensional (3D) dendrite structures, featuring abundant step and edge sites. The various factors affecting the morphology and the ratio of 2D to 3D dendrites of Pt were determined by TEM analysis. The ratio of 2D to 3D Pt dendrites depends on the amount of PVP employed and has a direct influence on the electrochemically active surface area (ECSA) and HER activity. Namely, the prepared Pt/PFG sample with the highest density of 2D Pt dendrites exhibits the highest HER activity due to its high ECSA. The performance of Pt/PFG13 (prepared keeping the PVP:Pt ratio as 13:1) was compared with that of commercial 40 wt% Pt/C, and the Pt/PFG13 sample exhibited superior current density (−424 mA/cmgeo 2 for Pt/PFG13 and –242 mA/cmgeo 2 for commercial 40 wt% Pt/C at −1.5 V vs. Hg/HgO; approximately 1.8 times higher) and catalytic stability, implying that these parameters are positively correlated with the increased number of step and edge sites. Graphical abstract: Image 1 Highlights: High voltage electrochemical reduction method is newly developed for synthesizing nanoparticle. The prepared Pt nanoparticle have an electrocatalytically active 2D and 3D dendrite structure. The ratio of 2D to 3D Pt dendrites depends on the amount of PVP employed. The HER performance and stability of the prepared Pt dendrite on PFG is superior to commercial Pt/C.